ADOPSI INOVASI PENGELOLAAN TANAMAN TERPADU SISTEM TANAM JAJAR LEGOWO DAN KESEJAHTERAAN RUMAHTANGGA PETANI PADI (KASUS DI DESA PALAS JAYA DAN PULAU TENGAH KECAMATAN PALAS KABUPATEN LAMPUNG SELATAN) - Viranita Sismiari; Tubagus Hasanuddin; Begem Viantimala (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The purposes of this study were to determine the level of adoption of integrated crop management ’jajar legowo’ innovation in lowland rice cultivation, related factors, household income of lowland rice farmers after adopting the innovation, and to know the relationship between the adoption rate and the welfare of farmers. This research was conducted in Palas Jaya and Pulau Tengah Villages, Palas District, South Lampung Regency. Respondents were 68 rice farmers taken proportionally and randomly from each of the two villages. Adoption of ‘jajar legowo’ planting system in Palas Jaya and Tengah Tengah Villages of Palas District, South Lampung Regency was high (92.64 percent). Factors related to the adoption were characteristics of innovation, characteristics of farmers, the role of extension workers, and household welfare of wetland rice farmers. Annual household incomes of rice farmers adopting integrated crop management were Rp24,251,188.24 consisting of Rp18,310,012 from on farm, Rp5,058,823.53 from nonfarm and Rp882,352.94 from off-farm activities. There is a significant correlation between the level of adoption of innovation in integrated crop management of paddy rice and household welfare of rice farmers.Key words: adoption, income, welfare